Meta Analysis: Health Belief Model on Cervical Cancer Screening among Women of Reproductive Age - Afifa Intifadha Habibatullah; Adetya Wulandari; Aurina Firda Kusuma Wardani (Journal of Health Promotion and Behavior, 2021)
Background: Cervical cancer is one of the most common cancers and the most common cause of death in women worldwide. Health Belief Model is a theoretical model that explains the influence of beliefs on a person's health behavior, including cervical cancer prevention behavior. This study aims to determine the effect of the HBM construct on cervical cancer screening behavior among women of childbearing age based on a primary study conducted by previous researchers.Subjects and Method: This study is a systematic review and meta-analysis with PICO as follows: Population: women of reproductive age, Intervention: HBM constructs of high perceived severity and high self-efficacy. Comparison: low perceived severity and low self-efficacy. Outcome: cervical cancer screening. The articles used in this study were taken from several databases, namely Google Scholar, Pubmed, SpringerLink, Scopus, and SAGE. The keywords used for the search were “Health Belief Model” AND “Cervical Cancer Screening” OR “Cervical Cancer Test” OR “Pap Smear” OR “Papanicolaou Test” OR “VIA Test” OR “Visual Inspection Acetic-Acid” AND “Adjusted Odds Ratio” OR aOR. Inclusion criteria were full-text articles in English and Indonesian with a cross-sectional study design, population of women of childbearing age, and cervical cancer screening as an outcome, analyzed multivariately by including adjusted Odds Ratio/aOR. Articles were selected using the PRISMA flow diagram and analyzed using the Review Manager 5.3 application.Results: A total of 7 cross-sectional studies from Europe, Asia, Africa, and Australia were reviewed and meta-analyzed. The results showed that women of childbearing age with high perceived severity were 1.61 times more likely to have cervical cancer screening than those with low perceived severity (aOR = 1.61; 95% CI = 1.11 to 2.34; p = 0.01). The data also showed that women of childbearing age with high self-efficacy were 5.91 times more likely to undergo cervical cancer screening than women with low self-efficacy (aOR= 5.91; 95% CI= 3.25 to 10.75; p<0.001).Conclusion: Severity perception and self-efficacy are predictors for tertiary prevention of type 2 Diabetes Mellitus.Keywords: health belief model, perceived severity, self-efficacy, cervical cancer screening.Correspondence:Afifa Intifadha Habibatullah. Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: afifa.pink2@gmail.com. Mobile: 085728146915.Journal of Health Promotion and Behavior (2021), 06(04): 307-317DOI: https://doi.org/10.26911/thejhpb.2021.06.04.05